2005
DOI: 10.1159/000082428
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Renal Artery Hemodynamics in Normal Fetuses Using the Color Doppler Method

Abstract: Objective: From analysis of fetal renal artery hemodynamics, we attempted to reveal renal glomerular and tubular function in normal fetuses during pregnancy. Design: The study included 36 cases of normal fetuses from the 20th to the 40th week of gestation; Vmax (the systolic peak velocity of main renal artery), Vmean (time averages of trace of peak velocity) blood flow were initially measured between 20 and 24 weeks of gestation and every 4 weeks thereafter. The measurement was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(17 reference statements)
5
7
1
Order By: Relevance
“…The trends for specific gestational ages were in agreement with other studies [10,15,16], although the absolute values differed.…”
Section: Discussionsupporting
confidence: 92%
“…The trends for specific gestational ages were in agreement with other studies [10,15,16], although the absolute values differed.…”
Section: Discussionsupporting
confidence: 92%
“…Most of them were type III. This finding is similar to the previous studies [4,9], which found that all 3 patterns of renal artery Doppler can be seen among normal fetuses, although the percentages of such patterns differed from those in our study. An explanation may lie in the differences in gestational age in each study and the small sample size in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…An explanation may lie in the differences in gestational age in each study and the small sample size in previous studies. Most of cases in previous studies were fetuses in the third trimester of pregnancy [4,9]. Interestingly, we found that during the second trimester of pregnancy the fetal artery Doppler indices, including of PI, PSV, S/D and RI (with AEDV removed), each increased significantly with gestational age, but the increase in EDV (with AEDV removed) with gestational age was not significant.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…[10] The fetal middle cerebral artery (MCA) can directly reflect blood circulation of the fetal brain, and the S/D, PI, and RI are the hemodynamic indices of brain circulation. [11] The fetal renal artery (RA) also tends to directly reflect blood perfusion of the fetal kidney. The RA is one of the organs sensitive to hypoxia and one of the first organs to have endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%